Uniform-sized insulin-loaded PLGA microspheres for improved early-stage peri-implant bone regeneration - Xing Wang; Feng Qi; Helin Xing; Xiaoxuan Zhang; Chunxiang Lu; Jiajia Zheng; Xiuyun Ren (Taylor & Francis Group, 2019)
Poor initial stability at the first four weeks after surgery is becoming the major causes for metal implant failure. Previous attempts neglected the control release of insulin for the bone regeneration among nondiabetic subjects. The major reason may lie in the adverse effects, such as attenuated bone formation, hypoglycemia or hyperinsulinemia, that caused by the excessive insulin. Thus, spatiotemporal release of insulin may serve as the promising strategy. To address this, through solvent extraction (EMS), solvent evaporation (SMS) and cosolvent methods (CMS), we prepared three types of PLGA microspheres with various internal structures, but similar size distribution. The effects of the preparation methods on the properties of the microspheres, such as their release behavior, degradation of molecular weight, and structural evolution, were investigated. Human bone marrow mesenchymal stromal cells (BMSCs) and rabbit implant models were used to test the bioactivity of the microspheres in vitro and in vivo, respectively. The result demonstrated that these three preparation methods did not influence the polymer degradation but instead affected the internal structural evolution, which plays a crucial role in the release behavior, osteogenesis and peri-implant bone regeneration. Compared with EMS and CMS microspheres, SMS microspheres exhibited a relatively steady release rate in the first four weeks, which evidently stimulated the osteogenic differentiation of the stem cells and peri-implant bone regeneration. Meanwhile, SMS microspheres significantly enhanced the stability of the implant at Week 4, which is promising to reduce early failure rate of the implant without inducing adverse effects on the serum biochemical indices.